FMtree: a fast locating algorithm of FM-indexes for genomic data - Cheng, Haoyu; Wu, Ming; Xu, Yun (Bioinformatics, 2018)
Abstract Motivation As a fundamental task in bioinformatics, searching for massive short patterns over a long text has been accelerated by various compressed full-text indexes. These indexes are able to provide similar searching functionalities to classical indexes, e.g. suffix trees and suffix arrays, while requiring less space. For genomic data, a well-known family of compressed full-text indexes, called FM-indexes, presents unmatched performance in practice. One major drawback of FM-indexes is that their locating operations, which report all occurrence positions of patterns in a given text, are not efficient, especially for the patterns with many occurrences. Results In this paper, we introduce a novel locating algorithm, FMtree, to fast retrieve all occurrence positions of any pattern via FM-indexes. When searching for a pattern over a given text, FMtree organizes the search space of the locating operation into a conceptual multiway tree. As a result, multiple occurrence positions of this pattern can be retrieved simultaneously by traversing the multiway tree. Compared with existing locating algorithms, our tree-based algorithm reduces large numbers of redundant operations and presents better data locality. Experimental results show that FMtree is usually one order of magnitude faster than the state-of-the-art algorithms, and still memory-efficient. Availability and implementation FMtree is freely available at https://github.com/chhylp123/FMtree. Supplementary information Supplementary data are available at Bioinformatics online.